Ruang Kelas Sebagai Ruang Dinamis Guna Merancang Lingkungan Belajar yang Mendukung Kreativitas Siswa - Fitriya Ichda Setiyawati; Diah Indri Lestari; Berlian Marsha Malihah; Singgih Bektiarso (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses various efforts and strategies in classroom management that aim to improve students' motivation, discipline and learning effectiveness. Using descriptive qualitative research methods and literature studies, this article analyzes recent studies that show that good classroom management can significantly contribute to improving students' learning abilities. Various approaches, such as the use of learning through play, teachers' creativity in creating a dynamic learning environment, and students' involvement in school policy-making, are identified as key factors in creating a positive learning atmosphere. This research also highlights the importance of classroom climate management and the role of teachers in building good interactions between students. The results of this study are expected to provide insights for educators and education managers in designing more effective classroom management strategies.